Does Worker Wellbeing Affect Workplace Performance? - Alex Bryson; John Forth; Lucy Stokes (Institute for the Study of Labor (IZA), 2015)
This paper uses linked employer-employee data to investigate the relationship between employees' subjective well-being and workplace performance in Britain. The analyses show a clear, positive and statistically-significant relationship between the average level of job satisfaction at the workplace and workplace performance. This finding is present in both cross-sectional and panel analyses and is robust to various estimation methods and model specifications. In contrast, we find no association between levels of job-related affect and workplace performance.
Keywords: J28; 330; subjective wellbeing; job satisfaction; job-related affect; workplace performance